Implementasi Intervensi Berbasis Self-Determination Theory pada Remaja di Bawah Pengawasan Panti Asuhan X - Samuel Fredericko Sherloe; Rasyatul Aini; Hanifatul Aisyah; Astri Anggraini Hapsara Wibowo (YASIN, 2026)
Basic psychological needs in Self-Determination Theory (SDT), which include autonomy, competence, and relatedness, play an important role in supporting adolescents’ psychological development. However, adolescents under the supervision of an orphanage may face obstacles in fulfilling their basic psychological needs due to limited personal support and the dynamics of the caregiving environment. This study aims to support the fulfillment of the basic psychological needs of adolescents under the supervision of Orphanage X through an SDT-based intervention program. This study used observation, interviews, and pre-test and post-test measurements using the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS). The research participants consisted of eight adolescents aged 14–16 years who were selected based on pre-test results indicating high need frustration, low need satisfaction, or a condition in which frustration was higher than satisfaction in several aspects of basic psychological needs. The intervention program was implemented through several activities, namely “Mading Surat,” letter writing, “Content Creator Challenge,” “Poster Challenge,” and “Buku Mini Cita-Citaku.” The results show an increase in the average scores for autonomy satisfaction, relatedness satisfaction, and competence satisfaction after the implementation of the intervention. In addition, several aspects of frustration decreased among some participants, although changes in each participant showed different dynamics and did not always occur linearly. The conclusion of the study affirms that an SDT-based intervention program can be a relevant approach to help support the fulfillment of adolescents’ basic psychological needs in an orphanage environment. The implications of this study provide practical contributions for caregivers, educators, and social institutions in designing intervention activities that support adolescents’ autonomy, competence, and social relatedness in a more targeted manner.